Evaluación y multiplicación de trichoderma spp, en tres tipos de sustratos (arroz, arrocillo y arroz de cebada) con el efecto de tres luces (luz amarilla, azul y roja) en el cantón Latacunga, provincia de Cotopaxi, Campus Salache 2022- 2023. - Fraga Pilataxi, Darwin Arturo (2023)
This research project was carried out in the Salache campus laboratory, the multiplication of Trichoderma native to the Salache sector was begun, it was obtained from traps made at the Salache campus, and the multiplication process was carried out in 20 Petri dishes on PDA agar. It was left for 5 days in the incubator to multiply and obtain better spores, for applications in three different substrates, three substrates (rice, jungle rice, barley) were used, and each bag was filled with one of the substrates. A total of 9 bags per substrate were made and each was filled with 150 g for contamination, each substrate was contaminated with 8 ml of liquid Trichoderma, and the fungus was left to activate in the incubators for 7 days at a temperature of 27°C with three repetitions per substrate, giving a total of 27 substrates, three types of lights were determined (yellow, red, blue) where 3 different substrates were placed in a different light to determine their effect on Trichoderma, the yellow light with a temperature of 22 ° C, the effects of the biodegradability of the substrates were noted to see which is better in moments of contamination, it is better for the increase of the fungus, while the blue light of lower temperature spread in lower percentage or tended to pass.